Effect of empagliflozin on ketone bodies in patients with stable chronic heart failure - R. Pietschner (BMC, 2021)
Abstract Background Recent studies indicated that sodium glucose cotransporter (SGLT)2 inhibition increases levels of ketone bodies in the blood in patients with type 1 and 2 diabetes. Other studies suggested that in patients with chronic heart failure (CHF), increased myocardial oxygen demand can be provided by ketone bodies as a fuel substrate. Experimental studies reported that ketone bodies, specifically beta-hydroxybutyrate (β-OHB) may increase blood pressure (BP) by impairing endothelium-dependant relaxation, thereby leading to increased vascular stiffness. In our study we assessed whether the SGLT 2 inhibition with empagliflozin increases ketone bodies in patients with stable CHF and whether such an increase impairs BP and vascular function. Methods In a prospective, double blind, placebo controlled, parallel-group single centre study 75 patients with CHF (left ventricular ejection fraction 39.0 ± 8.2%) were randomised (2:1) to the SGLT-2 inhibitor empagliflozin 10 mg orally once daily or to placebo, 72 patients completed the study. After a run-in phase we evaluated at baseline BP by 24 h ambulatory blood pressure (ABP) monitoring, vascular stiffness parameters by the SphygmoCor system (AtCor Medical, Sydney, NSW, Australia) and fasting metabolic parameters, including β-OHB by an enzymatic assay (Beckman Coulter DxC 700 AU). The same measurements were repeated 12 weeks after treatment. In 19 of the 72 patients serum levels of β-OHB were beneath the lower border of our assay (< 0.05 mmol/l) therefore being excluded from the subsequent analysis. Results In patients with stable CHF, treatment with empagliflozin (n = 36) was followed by an increase of β-OHB by 33.39% (p = 0.017), reduction in 24 h systolic (p = 0.038) and diastolic (p = 0.085) ABP, weight loss (p = 0.003) and decrease of central systolic BP (p = 0.008) and central pulse pressure (p = 0.008). The increase in β-OHB was related to an attenuated decrease of empagliflozin-induced 24 h systolic (r = 0.321, p = 0.069) and diastolic (r = 0.516, p = 0.002) ABP and less reduction of central systolic BP (r = 0.470, p = 0.009) and central pulse pressure (r = 0.391, p = 0.033). No significant changes were seen in any of these parameters after 12 weeks of treatment in the placebo group (n = 17). Conclusion In patients with stable CHF ketone bodies as assessed by β-OHB increased after treatment with empagliflozin. This increase led to an attenuation of the beneficial effects of empagliflozin on BP and vascular parameters. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT03128528).